STRATEGIC MANAGEMENT PROCESS IN PRIVATES UNIVERSITIES: A CASES STUDY - Diniz, Daniela Martins; Castro, José Marcio de (Revista de Administração da UFSM, 2011)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> The aim of this article is to describe and understand how Strategic Management is designed, implemented and monitored in private universities. The data analysis has revealed which factors have affected the Strategic Management process in these universities, its characteristics, the actors involved in this process and, finally, the relationship between planning and performance. The results have also shown that in two universities (cases A and B) their Strategic Management is already a mature process, which was designed in order to create a vision of the future and help both universities to deal with environmental pressures. By contrast, the third case (C) revealed that its Strategic Management has not reached yet the same level of maturity observed in the other two cases.